2019
DOI: 10.1186/s12882-019-1592-7
|View full text |Cite
|
Sign up to set email alerts
|

Muir–Torre syndrome: sebaceous carcinoma concurrent with colon cancer in a kidney transplant recipient; a case report

Abstract: BackgroundSebaceous carcinoma is a rare but progressive malignant skin cancer, and the incidence is approximately five times higher in post-transplant patients than in people who have not received kidney transplants. Sebaceous carcinoma is sometimes found concurrently with visceral cancers and a genetic abnormality, Muir–Torre syndrome. We report the case of a female kidney transplant recipient with sebaceous carcinoma concurrent with colon cancer 10 years after transplantation.Case presentationA 43-year-old w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…Previous studies have shown that sebaceous adenomas and carcinomas associated with Muir-Torre syndrome show negative staining in both compartments of the tumor. 6 , 7 , 8 This discrepancy suggests that the sebaceous neoplasms in the current case did not originate from a germline mutation, an observation which may be useful in terms of genetic counseling of affected patients.…”
Section: Discussionmentioning
confidence: 66%
“…Previous studies have shown that sebaceous adenomas and carcinomas associated with Muir-Torre syndrome show negative staining in both compartments of the tumor. 6 , 7 , 8 This discrepancy suggests that the sebaceous neoplasms in the current case did not originate from a germline mutation, an observation which may be useful in terms of genetic counseling of affected patients.…”
Section: Discussionmentioning
confidence: 66%
“…This patient developed cancers 10 years after transplantation, during which time she received immunosuppressive medication consisting of tacrolimus, methylprednisolone, and mycophenolate mofetil. These authors concluded that immunosuppressant therapy could play a role in the development of malignancies in MTS patients [ 15 ]. The development of neoplasms because of immunosuppressive agents should not be underestimated.…”
Section: Discussionmentioning
confidence: 99%
“…The development of neoplasms because of immunosuppressive agents should not be underestimated. Tacrolimus and cyclosporine, both calcineurin inhibitors, have been reported to cause tumor progression, and switching patients to different drugs, such as mammalian target of rapamycin inhibitors, decreases tumor formation [ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Muir-Torre syndrome-associated sebaceous neoplasms have been described in 11 immunosuppressed renal transplant patients with Muir-Torre syndrome (Table 5), [13][14][15]24,32,35,36,38]. This includes one woman who was 43 years old when her sebaceous carcinoma occurred, and 8 men (ranging in age from 37 years to 81 years-median 47 years) when their sebaceous neoplasm occurred).…”
Section: Muir-torre Syndrome-associated Sebaceous Neoplasms In Renal ...mentioning
confidence: 99%